PENGARUH TEBAL DINDING TERHADAP STABILITAS DINDING PENAHAN TANAH PADA RENCANA RETAINING WALL JEMBATAN PEMUDA KECAMATAN SEBULU - udin, Saleh (KURVA S JURNAL MAHASISWA, 2014)
Landslide which occurred on the road caused by the movement of the soilmust be corrected immediately and must be addressed so that it does notinterfere with the performance of the road which is the lifeblood and drivingforce with establishment road section Youth Sebulu Ilir in District Sebulu, insome parts experiencing landslides due to the instability of the soil , so thatneeds to be addressed. Avalanche that occurred on these roads in the form oferosion of the road that could potentially lead to these roads cut off, so we needa quick and appropriate action in dealing with avalanche that occurred onthese roads.To limit the breadth of the scope of the discussion in a study that is toobroad, so in this study given the constraints that are more focused on the thingsof calculating the dimensions of retaining walls using a type counterfort, loadsthat work is the traffic load, the load pressure of the soil and earthquake loads,variations in wall thickness used was 0,450 meters and 0,350 meters long, 15meters high segments of the wall 3,5 meters, the quality of concrete used isK.275, or 275 kg/cm2.From the calculation results can be that the greatest axial force KNamounted 1330,0729 and 1321,9418 of the largest lateral force KN. Theinfluence of the wall thickness of the rolling and sliding penagruh significant,where the thicker the wall, the greater the ability of walls to withstand slidingbolsters and vice versa